2009
DOI: 10.1179/136485909x384956
|View full text |Cite
|
Sign up to set email alerts
|

Ecological aspects of the free-living ticks (Acari: Ixodidae) on animal trails within Atlantic rainforest in south–eastern Brazil

Abstract: In a recent ecological study of the ticks on animal trails within an area of Atlantic rainforest in south-eastern Brazil, Amblyomma aureolatum, A. brasiliense, A. incisum, A. ovale and Haemaphysalis juxtakochi were found questing on the vegetation. Most of the ticks recorded by a small, man-made dam on the forest border were A. dubitatum but a few A. brasiliense and A. cajennense, one A. incisum and one H. juxtakochi were also found. The seasonal activity of the ticks indicated that A. incisum and A. brasilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
22

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 19 publications
4
49
0
22
Order By: Relevance
“…The predominance of this ixodid on the campus is also corroborated by Silveira (2010), who correlated greater occurrence of A. cajennense on the UFRRJ campus with environments with high levels of anthropic activities and the presence of horses and capybaras. Previous reports also correlated the high degree of anthropization with the presence of this ixodid (LABRUNA et al, 2001;SZABÓ et al 2009) because this species is less sensitive to changes in the ecological structure of the area, which relates mainly to the availability of wild hosts (CANÇADO et al, 2008). Rojas et al (1999) also reported that A. cajennense was the dominant ixodid in captures performed in special protection areas in the cerrado (savanna-like terrain).…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of this ixodid on the campus is also corroborated by Silveira (2010), who correlated greater occurrence of A. cajennense on the UFRRJ campus with environments with high levels of anthropic activities and the presence of horses and capybaras. Previous reports also correlated the high degree of anthropization with the presence of this ixodid (LABRUNA et al, 2001;SZABÓ et al 2009) because this species is less sensitive to changes in the ecological structure of the area, which relates mainly to the availability of wild hosts (CANÇADO et al, 2008). Rojas et al (1999) also reported that A. cajennense was the dominant ixodid in captures performed in special protection areas in the cerrado (savanna-like terrain).…”
Section: Discussionmentioning
confidence: 99%
“…Como os animais domésticos (Pereira et al 2000), animais selvagens (Szabó et al 2007(Szabó et al , 2009) e o próprio homem compartilham inúmeras enfermidades, o acesso livre desses três elementos às APPs facilitará a transmissão de doenças, podendo causar grandes danos à fauna (Szabó et al 2003, Tiemann et al 2005, problemas econômicos para as criações animais (Araújo Júnior et al 2010) e o surgimento de zoonoses emergentes em humanos (Machado et al 2006). …”
Section: Acesso De Pessoas E Animais Domésticos As Appsunclassified
“…A ocorrência destes carrapatos em animais silvestres tem sido reportada nos diferentes biomas brasileiros (Aragão 1936, Labruna et al 2005, Szabó et al 2009), porém na Caatinga, uma região de grande diversidade de fauna e flora, a fauna de carrapatos tem sido pouco estudada.…”
Section: Introductionunclassified